2006
DOI: 10.1190/1.2194892
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of the capacitive resistivity technique

Abstract: Capacitive resistivity (CR) is an emerging geophysical technique designed to extend the scope of the conventional methodology of DC resistivity to environments where galvanic coupling is notoriously difficult to achieve, for example across engineered structures (roads, pavements), hard rock, dry soil or frozen ground. Conceptually, CR is based on a four-point array capacitively coupled to the ground. Under A parametric study of the complex quasi-static transfer impedance reveals the existence of a restricted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
113
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 21 publications
(29 reference statements)
2
113
0
20
Order By: Relevance
“…The application to archaeological studies of such an capacitively coupled approach and its equivalence to ERI are shown in Tabbagh et al (1993); the underlying theory of this equivalence is reviewed in Kuras et al (2006). However, both studies are based on a quasi-static approach employing point poles instead of sensors with finite dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The application to archaeological studies of such an capacitively coupled approach and its equivalence to ERI are shown in Tabbagh et al (1993); the underlying theory of this equivalence is reviewed in Kuras et al (2006). However, both studies are based on a quasi-static approach employing point poles instead of sensors with finite dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling is then largely confined to the surface of the plate and, on the scale of the four-point array, the point-pole condition is approximately fulfilled so that a DC geometric factor can be calculated. Another conceivable type of capacitive sensor is the capacitive line antenna (Timofeev et al, 1994), but interpretation of measurements is not trivial as the capacitance of such antennas is evenly distributed across their entire length (Kuras et al, 2006). In this paper, we will therefore focus on the use of plate-wire sensors.…”
Section: The Capacitive Resistivity Techniquementioning
confidence: 99%
“…Methodology, basic physics and the advantages and limitations of capacitive resistivity were the subject of a recent paper by the same authors (Kuras et al, 2006). …”
Section: The Capacitive Resistivity Techniquementioning
confidence: 99%
See 2 more Smart Citations